ARISTOTELIAN PROCLUS: Using the Analytics against the Topics to interpret the Parmenides - Butorac, David (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2020)
Proclus, while interpreting the dialectical method of the Parmenides, makes the astonishing claim that Aristotle at Prior Analytics I 27 had imitated Plato here, but that, of course, what Plato laid out was more complete. This remark is important in three ways: first, this is the only surviving case where a connection is made between the Neoplatonic interpretation of the method of the Parmenides and Aristotle’s Analytics; second, it provides a key to understand how Proclus interpreted the method; third, it reveals the increasing comfort – or decreasing antagonism – the later Neoplatonists had towards Aristotle. What I would like to do is to examine how Alexander interprets this passage, and in particular I will examine his development of per se predication here, how Proclus develops this in the context of the Parmenidean method and compare this to Philoponus’ commentary on this passage.